Formulasi Dan Uji Sifat Fisikokimia Sediaan Krim Ekstrak Daun Katuk (Sauropus Androgynous (L.) Merr.) Dengan Variasi Konsentrasi Asam Stearat - Erin Dwi Artanti; Fara Azzahra (Program Studi Farmasi UNAJA, 2022)
Abstract Background: Katuk leaf extract is formulated into a cream preparation to facilitate its use. Cream preparations need a base, the base used is stearic acid with variation concentrations of F1 (10%), F2 (12,5), and F3 (15%). Formulation and evaluation of cream preparations need to ensure that cream preparations have good quality so that their pharmacological effects can be achieved. Objective: The study aims to determine the physicochemical properties of the preparation of katuk leaf extract cream with variations in the concentration of stearic acid. Method: Experimental research using the Posttest Only Design method by testing the physicochemical properties of the cream of katuk leaf extract with variations in the concentration of stearic acid. Results: The result showed that the cream of katuk leaf extract in the 3 formulas was green, had a distinctive smell, was homogeneous, had a slightly thick form at F1 and thick at F2 and F3. The result of the pH values and the diameter of the spread of cream preparations on F1,F2, and F3 respectively were in the range of 7,22 ± 0,04 – 7,15 ± 0,06 and 6,49 ± 0,14 cm - 5,50 ± 0,52 cm. These result meet the requirements of pH and diameter of spread. Conclusion: The conclusion of the study is that the preparation of katuk leaf extract cream with various concentrations of stearic acid met the requirements for physicochemical properties which included organoleptic, homogeneity, pH and diameter of spread. Variations in the concentration of stearic acid affect the diameter of the spread.